APLIKASI TERDISTRIBUSI UNTUK PENGELOLAAN PENELITIAN BERBASIS WEB PADA LEMBAGA PENELITIAN DAN PUBLIKASI ILMIAH UNTAR - Rico Darmanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
research and scientific publications is an application that can assist in the process of the research report in Tarumanagara University The purpose of this application is to simplify the research process conducted by researchers and reviewers and to monitor the progress of the research done by the lecturers in UNTAR. The application is design ed using System Development Life Cycle and Waterfall method. The application is tested using blackbox testing methods and User Acceptance Test. Key words Research Institutes and Scientific Publications, System Development Life Cycle, Tarumanagara University, Waterfall method